Reconstructing Complex Societies. An Archaeological Colloquium. Held at Massachusetts Institute of Technology, April 29-30, 1972. Organized for the Cambridge Archaeology Seminar by Miranda C. Marvin - Lawrence E. Stager - Anita M. Walker
N. D., copyright 1974; Robert McC. Adams, The Mesopotamia Social Landscape, with comments by W. L. Moran and discussion (p. 1-20) [37:878]; G. E. Wright, The Tell: Basic Unit for Reconstructing Complex Societies in the Ancient Near East, with comments by Jean Perrot (p. 123-131).